Numerical simulation of heat and fluid flow through silicon-based microchannel with different surface roughness elements. (2017) - Bal, Sasmita; Mishra, Purna Chandra; Satapathy, Ashok Kumar
A physical problem of laminar flow through a silicon-based rectangular microchannel with designed surface roughness was solved numerically. Different shapes of the surface roughness such as: triangular, semicircular and trapezoidal were placed along the channel wall. The two-dimensional problem was modelled and simulated in the FLUENT's computational fluid dynamics (FLUENT-CFD) environments. The working fluid taken was incompressible in nature hence the no-slip condition was assumed. The inlet condition was taken as constant velocity and at the outlet was considered as zero gauge pressure as boundary conditions. The total number of grids taken was 12, 444 for the computational domain. FLUENT's segregated solver as an implicit solver was used. The effects of different working fluids such as: water, ethanol refrigerant and engine-oil on heat transfer were investigated for the same value of roughness pitch and height. The simulation results revealed that the Nusselt number variation along the channel was more for engine-oil than that for ethanol and water. This might be due to the fact that Nusselt number is a function of Prandtl number and the Prandtl number is comparatively high for engine oil.